Linguistic framing in central bank communications: a corpus-based study of Bank Indonesia policy statements - Arif Nugroho (Indonesian Journal of Language and Economic Discourse, 2026)
Background: Central bank communication has become a vital instrument for shaping expectations in emerging markets, where credibility and market confidence are highly sensitive to linguistic framing. Objective: The purpose of this study is to examine how Bank Indonesia constructs its policy messages through lexical choices, discursive strategies, and framing devices. Method: The research employs a mixed-method design, combining corpus linguistics (frequency, keyword, collocation) with critical discourse analysis and frame analysis, using a corpus of Bank Indonesia policy statements from 2015 to 2025. Results: The findings reveal three major results: first, lexical analysis shows concentrated use of keywords such as stability, inflation, and resilience; second, discourse analysis identifies rhetorical strategies of authority legitimation, risk normalization, and optimism projection; third, framing analysis demonstrates consistent reliance on stability, resilience, and growth-support narratives across policy documents. Implication: These results imply that Bank Indonesia’s communication operates not only as a technical information tool but also as a discursive mechanism for legitimizing authority and anchoring expectations. Novelty: This study contributes to the ways central bank communication operates as a strategic discursive mechanism that stabilizes market expectations through patterned lexical choices, framing consistency, and the projection of institutional authority.